Toward Peace-Loving Attitude Trough Education Character - Dalmeri Dalmeri; Antonius Atosokhi Gea (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Efforts to solve violence had been faced by multi treatments. Violence in education is action over the standar of ethic and rule in education, either physically or disturbing the rights of ones. The actors can be anyone, including the chief of school, teacher, staff , student, parents and even society. Violence in education is assumed as effect of certain condition. Externally or internally, and it might happen with any trigger. This paper aims to analyse the importance of character building through peace-loving attitude to revitalize the actors of education as evaluation of structure and culture in the educational world. Our educational world recently sometimes shows its arrogancy and even militaristic behavior. While the basic tenet of education is to appreciate the understanding of human behavior in order to be enlighted and free.